Uma ferramenta para o "acesso à justiça" : padronização ou convencionalização de termos-conceitos-jurídicos em Libras - Martins, Jéssica Santos Souza (2023)
There are many challenges for the Sign Language and Portuguese Translator and Interpreter (TILSP) when working in a legal context, due to the excessive formality and specialized and complex terminologies, which generate linguistic distance on a semantic-pragmatic level, highlighting (inter)intralingual problems. The specialized training of TILSP’s and the development of translation skills and competencies are essential, according to the arguments of Machado (2017), since their presence alone does not imply accessibility in the legal context. In this context, among all the challenges for TILSP's performance, the terminological issue stands out, since the legal vocabulary is already distant from citizens who have Portuguese as their first language. In this sense, it is proposed to investigate the correlation between the lack of terminological standardization in Libras and the lack of communicational accessibility of deaf signers in the legal context. The present research is affiliated with the precepts of Cognitive Linguistics (CL), starting from the studies of Cognitive/Lexical Semantics, going through pragmatic constructions and studies of polysemy, intending to investigate how the cognitive processing of TILSP occurs in relation to grammatical constructions (GOLDBERG, 1995; BYBEE, 2016) and radial categorization of linguistic schemes (LAKOFF, 1987) referring to legal terminologies, as well as the breach of the principle of linguistic cooperation (GRICE, 1982) as a result of the lack of standardization of legal terminologies in Libras, proposing the standardization of legal terms-signs that serve as a contribution to the creation of a Bilingual Legal Dictionary of Libras and Portuguese. The corpus was created from an activity developed in the subject of Translation and Interpretation in a Legal Context, taught by Prof. Dr. Flávia Machado, in the 6th period class of the Literature/Libras course (UFES). The method is a qualitative proposal, based on data collection that will take place as follows: (1) filling out a questionnaire by students; (2) distribution of a judicial text among groups in the class; (3) selection of legal words with unknown meaning; (4) search for meaning in traditional and legal vocabularies; (5) proposal of term-legal signs, followed by the phonomorphological description generated in Libras. From the collection, the procedures for analysis were constituted as follows: (1) tabulation of legal vocabularies, dictionary meanings and grammatical applications; (2) selection of 5 legal concept terms from the corpus; (3) socialization and discussion about the proposals between deaf and hearing members, teachers and researchers of the LingCognit Research Group - Language and Cognition: translation and interpretative choices. Socialization aims to appreciate and validate the phonomorphological construction of grammatical use in Libras and the semantic-pragmatic correspondence that the legal term- concept can be standardized in the Judiciary. Considering the final result, it appears that it is necessary to standardize legal terminologies for use in Libras in a proposal that takes into account the grammatical, phonomorphological and semantic-pragmatic aspects of Libras, in a construction that involves a multidisciplinary team